Pengolahan Susu Kambing Di Desa Bangelan, Kecamatan Wonosari, Kabupaten Malang (TEKAD : Teknik Mengabdi, 2024)
One of the communities with advanced technology in Wonosari District, Malang Regency, is Bangelan Village. It makes use of its natural resources. The ability of Bangelan Village's livestock to create goat milk products is one of its finest commodities. In Bangelan Village, the products made from goat milk are processed, which boosts earnings. The value of goods created from their original raw materials—goat's milk—increases when they are prepared as yoghurt, kefir, or milk candies. Etawa goat milk is the type of goat milk produced. Due to marketing barriers like not having a BPOM certificate and not pasteurizing products before they are developed, the productivity of processed goat milk products has stagnated. The control of processed goat